After the Race to the Top: State and District Capacity to Sustain Professional Development Innovation in Florida. Issue 2 (March 2023) - Akiba, Motoko; Howard, Cassandra
The Race to the Top (RTTT) program incentivized states to use innovation for systemwide improvement of student outcomes, but little is known about how RTTT-funded innovation was sustained after the RTTT program ended. This mixed-methods study examined state and district approaches to sustaining an international innovation called lesson study, a teacher-driven, collaborative, inquiry-based teacher learning process imported from Japan and promoted statewide in Florida. While the state's role in sustaining lesson study was limited, we found that districts that integrated lesson study into the district instructional system through a clear expectation and strategic adaptation, supported school and teacher ownership of lesson study practice, and provided necessary support and funding were more likely to sustain lesson study. In contrast, the districts that focused on implementation fidelity and district-led facilitation eventually phased out lesson study. Policy implications for sustaining federally funded professional development innovations are discussed.